تحسين أداء نقل بيانات الوسائط المتعددة باستخدام الجدولة الفعالة لبروتوكولات الزمن الحقيقي - محمد حجازية; بولس الخوري (Tishreen University, 2018)
تعد مشكلة جودة الخدمة في نقل بيانات الوسائط المتعددة من أعقد وأهم المشاكل التي تواجه شبكات تبادل المعلومات في وقتنا الحالي والتي تتمثل بتزايد الطلب على استخدام وسائل التواصل الاجتماعي التفاعلية في الزمن الحقيقي وتزايد الطلب على خدمة الانترنت وتنوع متطلبات المستخدمين كتحميل بيانات الوسائط المتعددة، مشاهدة الفيديو , وغيرها عبر الشبكة. من أجل التغلب على هذه المشاكل وتحسين عملية نقل بيانات الوسائط المتعددة للوصول إلى مستوى جيد من سرعة نقل البيانات مع الحفاظ على أدنى مستوى ممكن من الأخطاء والتغلب على المشاكل الأكثر تأثيرا على هذا المجال كالتأخير الزمني وفقدان البيانات وغير ذلك، تم في هذا البحث اجراء دراسة تحليلية لأنظمة نقل بيانات الوسائط المتعددة واقتراح الحلول المثلى باستخدام الجدولة الفعالة لبروتوكولات الزمن الحقيقي. يُقدم في هذا البحث دراسة تحليلية ومقارنة لخوارزميات الجدولة في الزمن الحقيقي التي يمكن الاستفادة منها في مجال البحث. وتم تحليل نتائج المحاكاة للخوارزميات على السيناريوهات التي تم دراستها حيث تم استخدام البرنامج OPNET لإنجاز المحاكاة. تمت الدراسة في البحث على شبكتين متماثلتين نسبيا في البنية مع اختلاف عدد الأجهزة المكونة فإحداها جهاز مع جهاز والثانية عشرة أجهزة مع عشرة أجهزة وتمت دراسة عدة سيناريوهات على ثلاثة أنواع من الجدولة First In First Out(Fifo) - Weighted Fair Queuing (Wfq)- Priority Queuing(Pq) وعلى حجوم مختلفة للفيديو المرسل 120*128Pixel 128*240Pixel 240*352 Pixel وبدقة مختلفة وتم بعد ذلك الحصول على العديد من النتائج التي تدعم البحث وتدعم امكانية امثليه اختيار نوع الجدولة المناسب لتحسين واقع نقل بيانات الوسائط المتعددة. وتم التوصل في نهاية الاستقراء للنتائج أن خوارزمية الجدولة الأمثل هي خوارزمية PQ التي تتناسب مع جميع السيناريوهات. The problem of the quality of service in the transfer of multimedia data is of the most complex and the most important problems that facing the networks at the present time. which is increasing demand for the use of social media and interactive in real time, and the increasing demand for Internet service and the variety of user requirements as downloading multimedia data, watching videos, and other cross the network. In order to overcome these problems and improve the process of transferring multimedia data, to reach a good level of data transfer while maintaining the lowest possible level of errors and overcome the most impact on this field problems of jitter and data loss and others, We study and analyze multimedia data transmission systems and find technical solutions that optimized using the effective scheduling of real-time protocols. Our research over several sinarios and steps were interrelated. In the beginning, we study the theory and analytical about what is provided by the reference studies about the framework of this research. We have studied and compared the scheduling algorithms in real time that can be used in our research The results that we get from these algorithms on the scenarios that we have applied to the renowned simulation software OPNET. Two networks is used in this study that is relatively identical in structure with a different number of devices. One of these networks is one device with another one device. The other network is ten devices with ten devices. The networks has several scenarios to study on. Where we have three types of scheduling First In First Out(FIFO) - Weighted fair queuing (WFQ)- Priority queuing(PQ) and the different beats of the size of the video sender 120 * 128Pixel 128 * 240Pixel 240 * 352 Pixel and we got a lot of results that support our research supports our choice in the selection of the optimum type of scheduling to improve the reality of multimedia data transfer. We have reached the end of the extrapolation of the results to be the optimum scheduling algorithm is the PQ algorithm to suit all scenarios.